CRISPR Interference Modules as Low-Burden Logic Inverters in Synthetic Circuits - Bellato, Massimo; Frusteri Chiacchiera, Angelica; Salibi, Elia; Casanova, Michela; De Marchi, Davide; Castagliuolo, Ignazio; Cusella De Angelis, Maria Gabriella; Magni, Paolo; Pasotti, Lorenzo (Frontiers in Bioengineering and Biotechnology, 2022)
The implementation of functional synthetic circuits with predictable behaviour in bacteria is limited by several sources, including the load exerted by heterologous expression of one or more circuit components. Transcriptional regulators, often adopted to engineer synthetic circuits, are affected by scalability and cell load issues. Such issues could be solved by CRISPR interference modules, implementing user-programmable logic inverters, in which the expression of guide RNA is expected to exert negligible cell load as no translation is required, with the only resource-consuming component being a constitutively expressed dCas9. This beneficial feature has been suggested in previous works (e.g.,Santos-Moreno et al.2020, Nat.Commun.,11:2746) but has never been characterized. We focus on this aspect by constructing a collection of synthetic circuits to quantify transfer function and cell load at varying guide RNA, dCas9 and target DNA copy number, and to optimize dCas9 expression. After confirming no relevant load occurs due to CRISPRi components, we demonstrated the wide tunability of their transfer functions. We finally demonstrated that the low-burden, high-scalability and easy-tunability features can be exploited to fix a non-functional circuit, and to easily add an input to an existing logic gate causing no burden. These findings will facilitate the rational design of synthetic circuits.